FORMULASI SEDIAAN GEL EKSTRAK ETANOL UMBI DAHLIA ( Dahlia variabilis )TERHADAP PERTUMBUHAN BAKTERI Stapylococcus aureus PENYEBAB INFEKSI KULIT - Zola Efa Harnis (Jurnal Penelitian Farmasi & Herbal, 2023)
Dahlia tubers (Dahlia variabilis) are plants that are often found in the higglands. The content in Dahlia tubers is able to inhibit microbial growth. The compound content of Dahlia tubers includes alkaloids, flavaanoids, sapnonins and tannins. One of the diseases caused by microbes is a skin infection. The purpose of this study was to make a gel preparation from the ethanolic extract of dahlia bulbs and to test whether the formulation was able to inhibit the growth of Stapylococcus aureus bacteria at concentrations of 4%, 6% and 8%. The extraction used in this research is the maceration method with 96% ethanol as solvent. Evaluation test of gel preparations and antibacterial activity test by discdiffusion method. Then the one way ANOVA test was carried out. The results showed different result in each formulation. Based on the average results of the antibacterial activity test, the inhibition zones of F) were 17,0 mm, F1 18,13 mm, F2 was 19,73 mm, and F3 8,23 mm. The results of this study conuluded that the extraction of Dahlia tubers had antibacterial activity due to the presence of an inhibitory zone around the paper disc in a petri dish. Further research needs to be done with other methods.